Development of Rental Application using Prototyping Method - Riyanti, Apriani; T, Taryana; Dirgantoro, Guruh Putro; Gunawan, I Made Agus Oka (PT.KARYA GEMAH RIPAH, 2024)
In the modern era of technology, it is crucial to have access to the most up-to-date technical advancements. However, not everyone has the means to regularly upgrade their gadgets to keep pace with these improvements. This phenomenon can be attributed to the exorbitant expenses and transitory demand for technology, particularly in emerging nations like Indonesia, where the rental sector remains inadequately developed. This research proposes the construction of a mobile phone and camera rental application named Quick-Rent. The application is created using the Prototyping method, which is a system development approach. The prototyping method was selected due to its ability to enable developers to evaluate and enhance features depending on user feedback right from the outset of the design process. This application is specifically intended to enhance the efficiency of the leasing process by adapting system features based on user needs analysis. The findings indicated that certain system features were modified based on the user needs analysis. The system implementation process and the 7 scenario of blackbox testing confirmed the validity and usability of these features.